Use of images for early identification of water stress: BIBLIOGRAPHIC REVIEW - Alves, Renata Fernandes; Putti, Fernando Ferrari (Revista Brasileira de Engenharia de Biossistemas, 2022)
The instability of climatic events intimidates the development of crops at a global level, as it can cause serious economic and social consequences in the face of increased demand for food. In this scenario, the use of images for early identification of water stress is considered a form of non-destructive identification of physical, biochemical, and plant development-related responses. Water deficit is responsible for triggering a series of responses in the plant due to the increase in the production of Reactive Oxygen Species (ROS) and the accumulation of Abscisic Acid (ABA) that promotes the closing of the stomata, limiting the evaporative cooling capacity performed by the plant, given the increase in its leaf temperature. The present article investigates the relationship between the water deficit in the plant and the consequent increase in its leaf temperature.